Strategic Analysis of ČSOB - Poulík, Jan; Kupec, Václav; Krause, Josef, 1978-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Times are changing and nothing is as certain as before. The whole world is developing rapidly and from that arises the need to conduct a comprehensive analysis of one of the biggest and most established Czech banks. Československá obchodní banka a.s. must adapt their strategy accordingly, to accommodate for current events and this paper should assist in doing so. Main tools used in this thesis was the PESTEL analysis, Porters five forces analysis, Stakeholder analysis and lastly benchmarking with other competitors. As a final product a SWOT table was developed, gathering and applying previously obtained results. Based on the SWOT analysis, key suggestions were created to pinpoint the areas which should be a priority for ČSOB as of now. The results signed that ČSOB should focus on investing into AI technology, improve their marketing strategy or consider modifying their offered product portfolio. Under the assumption that ČSOB will be able to refine their mindset and adjust the strategical decisions to follow provided suggestions, only a bright future lies ahead.
Vedoucí práce: Václav Kupec
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses